EDUCATION MOVEMENT IN THE PREVENTION OF ELDERLY FALLS: TECHNIQUE IVALDO BERTAZZO (Fiep Bulletin - online, 2011)
The human aging is responsible for decreases in the organic functions, reducing the health and the life quality. A very serious problem which can lead the aged to incapacity, to low life quality and also to precocious death is the incidence of falls. Among others factors, theese falls occur due to the losses the aged show in movement coordination and in psychomotor and proprioceptivo stimulation. A set of tools which can possibly perform significant redcuction of aged people falls can be found in the method of Ivaldo Bertazzo called "Educação do Movimento" (Movement Education). In compliment, qualitative resources have been used, as an interview with the method author. The results point to comprove the efficiency of this methot application to prevent aged people falls.
Keywords: human aging; fall; education movement